SEMANGAT HUMANISASI PEREMPUAN MEMBIMBING REMAJA DALAM MENGENTASKAN KEMUNDURAN AKHLAK DI PADANGSIDIMPUAN UTARA - Asfiati Asfiati (Jurnal Kajian Gender dan Anak, 2020)
Teenagers have identity. Teenagers can be independent. Teenagers in North Padangsidimpuan have a population of 25% of the population of North Padangsidimpuan. Padangsidimpuan Utara is the center of the city. The population of North Padangisidmpuan consists of heterogeneous communities. Herogeneity is the cause of change and development. Change and development in adolescents. Teenagers are expected to be future counselors. Teenagers must be role models. Teenagers must avoid moral decline. Moral decline is indicated where adolescents are not able to control themselves. Adolescents who experience moral setbacks such as disobedience to parents, reduced enthusiasm for learning, arrogance and arrogance can be alleviated through the spirit of humanization of women. A woman who is subtle in language. A soft-spoken woman. Women who have a myriad of rahman and rahim. Women who are humanists, women who are rich in the treasures of empathy and egalitarianism. Humanist women can guide adolescents. Guiding youth to noble morals. A true and dedicated teenager. Teenagers who are involved and given the opportunity to participate. Guiding youth is part and responsibility of women. Women can lead and escort teenagers towards a future full of meaningfulness and excitement.